(untitled) (Journal of Current and Advance Medical Research, 2025)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most commonly prescribed and used for the treatment of pain and inflammation. Though these type of drugs contains many side effects, they are widely used. Objective: The aim of this study was to assess the prescribing pattern of NSAIDs in several pharmacies in Dhaka city. Methodology: This was a cross-sectional descriptive study conducted in Dhaka City of bangladesh during the period from July 2002 to June 2003. Total 8(eight) thanas were included in the study, namely Cantonment thana & Kafrul thana in the north part, Ramna thana & Motijheel thana in the south part, Khilgaon thana & Tejgaon thana in the east part, Mohammadpur thana & Mirpur thana in the west part. From each Thana, 2 (two) pharmacies were selected randomly. So, 16 (sixteen) pharmacies were selected for this study. Six hundred and eighty (608) prescriptions were considered for analysis as per the guideline of WHO/DAP 92.3 "How to investigate drug use in the community". For statistical analysis, SPSS software was used. Results: Among a total of 608 prescriptions, MBBS doctors prescribed 63.8%. Most of the study people (71.4%) were in the age group of 15-45 years. The majority (59.7%) were prescribed for males. The chief complaint/clinical diagnosis was mentioned as fever (20.1%). The most commonly prescribed NSAIDs were paracetamol (42.1), diclofenac sodium (21.9%); ibuprofen (10.4%); naproxen (5.9%); aspirin (1.6%), and other NSAIDs (18.1%) were prescribed respectively. NSAIDs were mentioned in generic names (4.9%) and in trade names (95.1.%) of total prescriptions respectively. In this study, the commonest prescribed dosage from NSAIDs were tablet/capsule (83.7%); syrup (9.0%); suppository (3.0%); injection (2.0%); suspension (1.8%); topical application (0.5%) were prescribed respectively. Conclusion: The patients usually consulted with MBBS doctors. The chief complaint/clinical diagnosis for which patients were prescribed NSAID is fever. The commonest prescribed NSAID is paracetamol. NSAIDs are mentioned in trade names in most cases. The commonest prescribed dosage from NSAIDs is tablet/capsule. Journal of Current and Advance Medical Research, January 2024;11(1):34-40